Antimicrobial Action of Esters of Polyhydric Alcohols - Conley, Anthony J. (1973)
A broth dilution method was used to determine the minimal inhibitory concentration of a series of fatty acid esters of polyhydric alcohols against gram-negative and gram-positive organisms. Gram-negative organisms were not affected. Gram-positive organisms were inhibited as follows. Of the monoglycerol esters, monoglycerol laurate was the most active. Esters of polyglycerols (tri-, hexa-, and decaglycerol esters) were generally active when the fatty acid had chain lengths of 8 to 12 carbon atoms. Sucrose esters, when active, except for laurate, are more active than the free fatty acid. The spectrum of antimicrobial action of esters of polyhydric alcohols is narrower when compared with the free acids.